Business competition related to the rapid test service for diagnosis of COVID-19 in hospitals in Surabaya, Indonesia - Izzah Khalif Raihan,; Sinar Ayu Wulandari,; Zainal Abidin Achmad , (Journal of Peace, Development and Communication, 2021)
The cost of rapid test in several hospitals in Surabaya, Indonesia, turns out to be a burden to patients due to the high-cost variations. These hospitals were suspected of a tying-in agreement which prohibited. This study aims to determine the impact of implementing the tying-in agreement and Komisi Pengawas Persaingan Usaha (KPPU) Regional IV Office’s efforts to deal with suspected violations related to the finding of the COVID-19 rapid test package offering with high prices in many hospitals. Article 15 paragraph (2) Law of the Republic of Indonesia No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business regulates tying-in agreements, potentially hindering business competition. The tying-in agreement on the rapid test facilities procurement is a violation of the law, and the perpetrators can go to prison. For this reason, researchers and the KPPU Regional IV Office cooperate in investigating the alleged practice of tying-in agreements that harm patients. This research method is qualitative through a statutory and conceptual approach, equipped with virtual search techniques on several online media news. The study did not find evidence in the form of a written document regarding the hospitals' tying-in agreement, so it was not sufficient to continue the investigation process. However, the study obtained patient admissions and brochures on the price of rapid tests, which had a detrimental effect on patients. The results of the evidence analysis of the existence of the rapid test's prices impacted the emergence of market access restrictions, creating monopoly markets, disguising price-fixing practices, and harming consumers of price variations. The study gave suggestions and considerations to Government for providing COVID-19 rapid test health facilities at the same price in several hospitals.